Penilaian Kinerja Pegawai Pemerintah Pemerintah dengan Perjanjian Kerja Berbasis Aplikasi di Sekretariat Daerah Kabupaten Kulon Progo - Setyawati, Novi; Muhammad, Adji Suradji (Journal of Indonesian Rural and Regional Government, 2025)
The digitalization of civil servant performance management has become a primary focus of bureaucratic reform in Indonesia. This study aims to analyze the effectiveness of the e-Kinerja application in supporting performance evaluations of Government Employees with Work Agreements (PPPK) at the Regional Secretariat of Kulon Progo Regency. A descriptive qualitative approach was applied, utilizing content analysis based on a comprehensive literature review of recent sources. The findings reveal that the implementation of e-Kinerja has delivered significant positive impacts, including enhanced transparency, consistency in evaluations, and administrative efficiency. Additionally, the application fosters a data-driven and performance-oriented work culture. Nevertheless, challenges persist, such as limited digital literacy among some employees, technical barriers, and resistance to shifting from manual practices. These results are reinforced by the Technology Acceptance Model (TAM) and Balanced Scorecard (BSC) frameworks, highlighting the importance of perceived usefulness, ease of use, and digital capacity building for sustainable system implementation. This study concludes that optimizing e-Kinerja requires integrating it with other information systems, simplifying its interface, and providing continuous digital literacy training for all employees.